The Effect of Supervisor’s Abuse on Hotel Employees’ Job Satisfaction, Affective Organizational Commitment and Work Engagement - Ampofo, E.T.; Ampofo, C.; Nkrumah, S.; Ameza-Xemalordzo, E.B. (Taylor & Francis Group, 2022)
Our study examines the impact of abusive supervision on affective organizational commitment (AOC). The study further examines work engagement (WENG) and job satisfaction (JSAT) as mediating mechanisms in the relationship between abusive supervision and AOC. The aforesaid hypothesized relationships were tested utilizing data gathered from frontline employees in upscale hotels in two waves in Ghana. We tested the hypothesized relationships using structural equation modeling. The findings reveal that abusive supervision is not significantly related to AOC. However, the findings demonstrate that WENG and JSAT fully mediate the relationship between abusive supervision and AOC. Theoretical and practical implications of the findings are discussed.
Research Article
Keywords: Abusive supervision; affective organizational commitment; job satisfaction; work engagement; hotel industry